Investigation of 23 Bile Acids in Liver Bile in Benign and Malignant Biliary Stenosis: A Pilot Study. (18th December 2019) - Rejchrt, Stanislav; Hroch, Milos; Repak, Rudolf; Fejfar, Tomas; Douda, Tomas; Kohoutova, Darina; Peterova, Eva; Bures, Jan
Abstract : Differential diagnosis between benign and malignant biliary stenosis can be difficult in clinical practice. Histology of biopsy specimens is often indeterminate. Laboratory markers (serum bilirubin > 75   μ mol / L, carbohydrate antigen 19-9 > 400   U / mL ) and the length of stenosis (>15 mm) can be helpful but are not specific enough. The aim of this study was to investigate bile acids in liver bile of patients with benign and malignant biliary stenosis and controls without stenosis. A total of 73 patients entered the study: 7 subjects with benign biliary stenosis (6 men, 1 woman; 68 ± 13 years old), 21 with malignant biliary stenosis (15 men, 6 women; 72 ± 14 years old), and 45 patients without biliary stenosis (22 men, 23 women; 70 ± 13 years old); out of those, 25 subjects have and 20 do not have choledocholithiasis. Twenty-three different bile acids were investigated by high-performance liquid chromatography/mass spectrometry. Serum total bilirubin was significantly higher in patients with malignant biliary stenosis compared with nonstenotic controls (p = 0.005 ). Significant relationship (r > 0.7 ) was found between several pairs of bile acids. Significantly lower bile acid concentrations in malignant biliary stenosis compared to controls without stenosis were found for GLCA (p = 0.032 ), GUDCA (p = 0.032 ), GCDCA (p = 0.006 ), GDCA (p = 0.031 ), GHCA (p = 0.005 ), TUDCA (p = 0.044 ), and TDCA (p = 0.036 ). Significant difference in cholic acid was found between benign and malignant stenosis (p = 0.022 ). Analysis of bile acids might be helpful in the differential diagnosis of malignant and benign biliary stenosis. More patients need to be enrolled in further studies so that the real diagnostic yield of bile acids can be determined.